2023
DOI: 10.1021/acs.analchem.2c04861
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning-Induced Isolation of Analyte and Analysis via Multiscaled Aqueous Two-Phase System

Abstract: Most fluorescence-based bioanalytical applications need labeling of analytes. Conventional labeling requires washing to remove the excess fluorescent labels and reduce the noise signals. These pretreatments are labor intensive and need specialized equipment, hindering portable applications in resource-limited areas. Herein, we use the aqueous two-phase system (ATPS) to realize the partitioning-induced isolation of labeled analytes from background signals without extra processing steps. ATPS is formed by mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, since the design options are so huge, constructing a design frame is necessary. (4) Broad applications from complex composition: Aqueous two-phase systems, known as the clean alternatives for traditional organic-water solvent extraction, make self-lubricating drops suitable for bioengineering processes or environment managements [34,98,99]. It is also notable that liquid crystalline solutions can broaden the applied range for fabrication of semiconductors, photo-alignment [6,95,100,101],…”
Section: Current Opinions and Open Questionsmentioning
confidence: 99%
“…However, since the design options are so huge, constructing a design frame is necessary. (4) Broad applications from complex composition: Aqueous two-phase systems, known as the clean alternatives for traditional organic-water solvent extraction, make self-lubricating drops suitable for bioengineering processes or environment managements [34,98,99]. It is also notable that liquid crystalline solutions can broaden the applied range for fabrication of semiconductors, photo-alignment [6,95,100,101],…”
Section: Current Opinions and Open Questionsmentioning
confidence: 99%
“…This segregation increases local concentrations, thus bolstering detection sensitivity. [16][17][18][19] It was reported that DNA could be enriched around seven times in ATPS and its detection of limit could be improved by 3.6-fold. 19 In living cells, a large variety of membraneless organelles are biomolecular condensates providing crowded compartments for biomolecules to fulfill their biochemical functions.…”
Section: Introductionmentioning
confidence: 99%